Unleashing the potential of morphotropic phase boundary based hybrid triboelectricpiezoelectric nanogenerator - Sugato Hajra; Aneeta Manjari Padhan; Basanta Kumar Panigrahi; Phakkhananan Pakawanit; Zvonko Jagli_i_; Naratip Vittayakorn; Yogendra Kumar Mishra; Sanghoon Lee; Hoe Joon Kim (My University, 2023)
Morphotropic phase boundary (MPB)-based ceramics are excellent for energy harvesting due to their enhanced physical properties at phase boundaries, broad operating temperature range, and ability to customize properties for efficient conversion of mechanical energy into electrical energy. In this work, Bi1–xNaxFe1–xNbxO3 (x = 0.20, 0.30, 0.32 and 0.40, BNFNO abbreviation) based ceramics were synthesized using a solid-state route and blended with Polydimethylsiloxane (PDMS) to achieve flexible composites. Various material characterization and energy harvesting were performed by designing a hybrid piezoelectric (PENG)-triboelectric (TENG) device. The voltage and current of PENG, TENG, and hybrid bearing same device area (2 cm × 2 cm) were recorded as 11 V/0.3 μA; 60 V/0.7 μA; 110 V/2.2 μA. The strategies for enhancing the output performance of the hybrid device were evaluated, such as increased surface area (creating micro-roughness and porous morphology) and increasing electrode size and multi-layer hybrid device formation. The self-powered acceleration monitoring was coupled with the artificial neural network strategies to predict the proper functioning of a linear motor. Further, the low-frequency-based wave energy is converted into electrical energy, confirming the usage of hybrid PENG-TENG devices as a base for battery-free sensors and blue energy harvesting.
Keywords: Nanogenerator; Phase boundary; Advanced Sensor and Energy Harvesting Materials